Entrepreneurial ecosystem as a spatially fluid concept: new territorial perspectives on entrepreneurship - Fischer, Bruno Brandão; Guerrero, Maribel; Mayer, Heike; Meissner, Dirk; Schäfer, Susann; Theodoraki, Christina (Small business economics, 2025)
Although the concept of entrepreneurial ecosystems (EE) is inherently spatial, the actual spatiality of these productive structures has been largely assumed rather than defined based on its formative processes. The oversimplification of the spatiality of EE seems to be a function of empirical reliance on available data, a situation that has generated broadly accepted definitions that delineate EE as fixed territories (be they cities, regions or even countries). Although important insights have been derived from such approaches, this has also hampered a fine-grained scrutiny on the fluidity of EE spatiality—especially along the course of EE evolutionary trajectories. Although most of its components are tied to regional territories, EE are not isolated spatial systems with no outside connections. Accordingly, addressing entrepreneurial ecosystems as such can cause an inadequate comprehension of how entrepreneurship-oriented relationships are organized between EE or between EE and the “hinterland.” These are the motivations that led us to come up with the Special Issue “Exogenous linkages of and between entrepreneurial ecosystems: Perspectives from Interregional and Global connectedness.” In this editorial, we present the articles included in this Special Issue and propose the idea of EE as “spatially-fluid” structures which affect the dynamics of EE configurations and, ultimately, their respective evolutionary trajectories.
Published online: 12. März 2025
Gesehen am 27.03.2025